2015
DOI: 10.12816/0009364
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Histological Studies on the Heart of Male Albino Rats Exposed to Electromagnetic Field and the Protective Role of Silymarin and/Orvitamin E.

Abstract: Aim of the work:This study aimed to determine the ameliorative effect of silymarin (SIL) and\or vitamin E (Vit.E) against changes induced by mobile phone radiation in the heart of male albino rats. Matrerial and methods:Total of 48 adult male albino rats were assigned for this study. The 1 st group served as control (n=6), the 2 nd group exposed to mobile phone generator radiation (900MHz) for 2hr/day 3days/week for two months, 3 rd group (+ve control) supplemented with SIL, 4 th group (+ve control) supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Signs or symptoms of any pathological process were not observed. The histopathology results of the heart agreed with the study by Zahkouk et al [27]. The kidney section of both control and group IV rats shows normal kidneys comprising glomeruli, renal tubule, interstitial tissues, blood vessels, and renal pyramid.…”
Section: Discussionsupporting
confidence: 90%
“…Signs or symptoms of any pathological process were not observed. The histopathology results of the heart agreed with the study by Zahkouk et al [27]. The kidney section of both control and group IV rats shows normal kidneys comprising glomeruli, renal tubule, interstitial tissues, blood vessels, and renal pyramid.…”
Section: Discussionsupporting
confidence: 90%
“…The antioxidant and protective properties of SM against a variety of free radical species have been proven in some studies (Negahdary et al 2015;Zahkouk et al 2015). In vitro studies have shown that the antioxidant properties of SM against oxidative stress injury are similar to the biological antioxidant glutathione (GSH) and even significantly greater than vitamin E (Surai 2015).…”
Section: Discussionmentioning
confidence: 99%